'Earth Eaters' and the Spirits of Omama: A Review of The Falling Sky. (23rd May 2016) - Wright, Robin
Abstract : Davi Kopenawa and Bruce Albert, The Falling Sky: Words of a Yanomami Shaman (trans. Nicholas Elliott and Allison Dundy; Cambridge, MA: Harvard University Press, 2013), xvii + 622 pp. [First published as La chute du ciel: Paroles d'un chaman yanomami (Paris: Plon, 2010)], 39.95 (Harvard); 28.83, ISBN 978-0-674-72468-6.